(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
A male came to the ER with wounds on his left arm after a vehicle incident. He was run over by the truck’s wheels on his left upper extremity until his whole arms were crushed. He had a massive crush injury on his whole left arm, no movement and pulse were detected. MESS Scoring resulted in score of 11, thus an indication for amputation. Blood examination showed increase of ureum and creatinine without previous kidney disease history. The patient was diagnosed with a crush injury of the upper extremity and Bywater’s Syndrome based on kidney involvement. He was consulted to the orthopedic department and was given fluid resuscitation, injections of analgesic, antibiotics, and Human Tetanus Immunoglobulin (HTIG). Proximal humeral amputation was performed. A second surgery later was performed to debride the wound due to contaminated necrotic tissues.